2015
DOI: 10.1007/jhep11(2015)192
|View full text |Cite
|
Sign up to set email alerts
|

Indirect determinations of the top quark mass

Abstract: Abstract:We give a complete analysis of indirect determinations of the top quark mass in the Standard Model by introducing a systematic procedure to identify observables that receive quantum corrections enhanced by powers of M t . We discuss how to use flavour physics as a tool to extract the top quark mass. Although present data give only a poor determination, we show how future theoretical and experimental progress in flavour physics can lead to an accuracy in M t well below 2 GeV. We revisit determinations … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 95 publications
0
5
0
Order By: Relevance
“…A similar comment applies to the very old idea pioneered in [81] in the case of the determination of the charm quark mass from K 0 −K 0 mixing and the top quark mass from B d −B d mixing [82] that has been extended to rare decays, in particular K + → π + νν and K L → π 0 νν, in [83]. It has recently been reconsidered in the context of general indirect determinations of m t in [84]. Even if such studies have some virtues, similar to the determination of |V cb | from rare Kaon decays [85], they necessarily assume that NP does not contribute to the processes used for such determinations at a measurable level and we should really hope that the nature will tell us soon that this assumption is wrong.…”
Section: Discussionmentioning
confidence: 87%
“…A similar comment applies to the very old idea pioneered in [81] in the case of the determination of the charm quark mass from K 0 −K 0 mixing and the top quark mass from B d −B d mixing [82] that has been extended to rare decays, in particular K + → π + νν and K L → π 0 νν, in [83]. It has recently been reconsidered in the context of general indirect determinations of m t in [84]. Even if such studies have some virtues, similar to the determination of |V cb | from rare Kaon decays [85], they necessarily assume that NP does not contribute to the processes used for such determinations at a measurable level and we should really hope that the nature will tell us soon that this assumption is wrong.…”
Section: Discussionmentioning
confidence: 87%
“…The ratios κ qµ ∼ (m MS t /m W ) 2 scale with the second power of the topquark mass in the MS scheme and, in principle, might be used to determine the top-quark mass in rare flavour processes under the assumption that κ qµ are not affected by NP contributions, which is still a possibility. A discussion of other examples in flavour physics that require the knowledge of CKM input and the corresponding prospects can be found in [53]. The MS mass is actually the preferred scheme for rare decay calculations over the pole scheme (OS), which however is used in many collider physics applications and provided in the PDG [32].…”
Section: The Issue Of M T In Rare Decaysmentioning
confidence: 99%
“…Top quark loops affect various lower-energy observables, that are thereby sensitive to the top quark mass. Previous work found that SM fits will not allow precise enough measurements of the top mass M t [21]. As a consequence, the only option to measure M t better is to measure it at future colliders.…”
Section: The Sm Vacuum (In)stabilitymentioning
confidence: 99%